Advances in industrial and labor relations. - Lewin, David; Gollan, Paul J. (Advances in industrial and labor relations, 2020)
Volume 25 of Advances in Industrial and Labor Relations (AILR) contains eight new peer-reviewed papers highlighting key aspects of employment relations from a global perspective. Topics discussed include dispute resolution through ombud and arbitration arrangements, union organizing in an informal economy, domestic and foreign firm labor market competition, occupational safety in coal mining, work and social protections in a platform economy, workforce training for older workers, and right-to-work law effects on the stock market. Consistent with previous AILR volumes, the papers in Volume 25 reflect a variety of quantitative and qualitative research methods. These range from primary research methods such as case studies, survey, interviews and historiography to longitudinal and cross-sectional research designs and theory building. Some of the research included in this volume was first presented at the 70th annual meeting of the Labor and Employment Relations Association (LERA) held in Baltimore, Maryland (USA) during June 2018.